The Philosophy of Du Marsais's Le Philosophe - Božovič, Miran (Filozofski vestnik, 2008)
The article considers the eponymous character of Du Marsais's Le Philosophe and examines his moral rationalism. In the eyes of Du Marsais's sage, the ways of virtue are not necessarily as painful as they might seem to those who are willing to stick to them solely in the hope of the promised post-mortem rewards, and the ways of vice are not necessarily as pleasant as they might seem to those who avoid them primarily out of fear of the threatened post-mortem punishment. The sage is not encouraged to be virtuous by the prospect of eternal pleasure, nor is he deterred from vice by the thought of eternal suffering. For him, virtuous behaviour, i.e., observing the rules of probity, is in itself a source of genuine pleasure; likewise, he finds sinful behaviour repelling in itself: since the sense of probity enters as much into the mechanical constitution of the sage as the enlightenment of the mind, any action contrary to probity is also contrary to his very nature.